2020
DOI: 10.1371/journal.pone.0239238
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of zika virus infection of human fetal cardiac mesenchymal stromal cells

Abstract: Zika virus (ZIKV) is a single-stranded RNA virus belonging to the family Flaviviridae. ZIKV predominantly enters cells using the TAM-family protein tyrosine kinase receptor AXL, which is expressed on a range of cell types, including neural progenitor cells, keratinocytes, dendritic cells, and osteoblasts. ZIKV infections have been associated with fetal brain damage, which prompted the World Health Organization to declare a public health emergency in 2016. ZIKV infection has also been linked to birth defects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…ZIKV can infect several body sites, including the eyes, cardiac tissue, the gastrointestinal (GI) system, reproductive tract, placenta, and central nervous system (CNS) (Figure 1) (Gasco & Muñoz‐Fernández, 2020; Rossi et al, 2020; Ryan et al, 2021; Zafar et al, 2021). The most common symptoms of acute ZIKV infection include fever, headaches, myalgias, rash, and conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
“…ZIKV can infect several body sites, including the eyes, cardiac tissue, the gastrointestinal (GI) system, reproductive tract, placenta, and central nervous system (CNS) (Figure 1) (Gasco & Muñoz‐Fernández, 2020; Rossi et al, 2020; Ryan et al, 2021; Zafar et al, 2021). The most common symptoms of acute ZIKV infection include fever, headaches, myalgias, rash, and conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
“…Since the onset of the ZIKV pandemic that began in 2015, a number of studies have revealed important information about how ZIKV targets specific cell types and proteins within the central nervous system (for reviews Khaiboullina et al, 2019 ; Sutarjono, 2019 ). The neurotropism of the virus may result from ZIKV using AXL, a tyrosine kinase receptor important in modulating the innate immune system ( Rothlin et al, 2007 ; Hafizi and Dahlbäck, 2006 ), to enter the brain ( Meertens et al, 2017 ; Rossi et al, 2020 ; Nowakowski et al, 2016 ). Single-cell RNA sequencing analyses have demonstrated that AXL is highly expressed in radial glia, endothelial cells, microglia, and astrocytes in the developing human cortex ( Nowakowski et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sendai virus, vesicular stomatitis virus, WNV, Enterovirus 71, influenza virus) [ 56 ]. TLR7 agonist Imiquimod, also identified in this work, suppresses ZIKV replication in human fetal cardiac mesenchymal stromal cells in a dose-dependent manner [ 40 ]. Known anti-ZIKV agents chloroquine and hydroxychloroquine repress ssRNAs-mediated activation of TLR7 signalling and the production of IFN-α [ 57 ].…”
Section: Discussionmentioning
confidence: 99%